Estimating slow pyrolysis products and standard enthalpy values of cellulignins from sugarcane bagasse, barley straw and Eucalyptus grandis: a comprehensive analysis using physical–chemical and thermal data - Bimestre, Thiago Averaldo [UNESP]; de Moraes Rocha, George Jackson; Nascimento, Viviane Marcos; Gomez, Edgardo Olivares; Rodrigues, Rita de Cássia Lacerda Brambilla; Canettieri, Eliana Vieira [UNESP] (Springer Nature, 2024)
Slow pyrolysis, a promising technique for converting lignocellulosic biomass into valuable products, is gaining significant attention due to its potential to address energy and environmental challenges. In this study, the focus is on three abundant biomass sources, namely sugarcane bagasse, barley straw, and Eucalyptus grandis, specifically targeting their cellulignin components. Cellulignins were obtained by partially removing hemicelluloses and lignin from biomass in the xylitol production process and serve as critical intermediates for various value-added products. The objective of this work is to estimate the products generated through slow pyrolysis and the associated standard enthalpy changes using a developed mathematical model. The methodology involves the characterization of the cellulignin samples through physicochemical and calorimetric analyses. The model showed that cellulignin derived from E. grandis, sugarcane bagasse and barley straw have similar trend. Carbon monoxide and methane equivalent mass yield increase and tar decreases as temperature increases. The predicted heat of pyrolysis is highly influenced by higher heating value (HHV) variations of cellulignins. The results for HHV of sugarcane bagasse was 19.91 MJ kg−1; for barley straw 18.99 MJ kg−1; and for E. grandis 21.49 MJ kg−1 respectively. The findings of this research contribute to the fundamental understanding of the slow pyrolysis behavior of cellulignins derived from sugarcane bagasse, barley straw, and E. grandis. The developed predictive model enables the estimation of product yields and compositions, facilitating process optimization and the design of efficient pyrolysis systems. This knowledge is vital for promoting the utilization of lignocellulosic biomass resources in a sustainable and economically viable manner.
Keywords: Biomass; Modeling; Pyrolysis products; Standard enthalpy